2003
DOI: 10.1109/tdei.2003.1207474
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of de arc discharge on ice surfaces

Abstract: A dynamic model for predicting dc arc behavior and critical flashover voltage of ice-covered insulating surfaces is presented. The model takes into consideration insulating geometry, pre-contamination level, and characteristics of ice layers. Assuming arc behavior as a time dependant impedance, it is possible to determine various arc characteristics such as time histories of leakage currents, potential gradient, channel radius, trajectory, propagation velocity and the energy injected into the zones free of ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 29 publications
4
48
0
1
Order By: Relevance
“…Voltage source Transformer The AC and DC minimum flashover and maximum withstand voltages of the insulator were determined under the conditions given in Table 3 These results show that the effect of polarity on the insulator string is around 25%, which is in accordance with the results presented in [32]. Consequently, from the results obtained, it can be concluded that the minimum flashover voltage is lower under DC-and AC than under DC+.…”
Section: Evaluation Sequencesupporting
confidence: 81%
See 4 more Smart Citations
“…Voltage source Transformer The AC and DC minimum flashover and maximum withstand voltages of the insulator were determined under the conditions given in Table 3 These results show that the effect of polarity on the insulator string is around 25%, which is in accordance with the results presented in [32]. Consequently, from the results obtained, it can be concluded that the minimum flashover voltage is lower under DC-and AC than under DC+.…”
Section: Evaluation Sequencesupporting
confidence: 81%
“…The flashover characteristics, as a function of surface conductivity, insulator length, and insulator diameter, determined by the dynamic model were quite satisfactory when compared to the experimental results of an insulating cylinder [32], [33], [125], [126], a short string of five IEEE standard insulators [32], [124], [125] and a post insulator [33], [125], [127] covered with artificial ice.…”
Section: Dynamic Modelsmentioning
confidence: 74%
See 3 more Smart Citations